Effectiveness of tranexamic acid on bleeding in conization - Albayrak Denizli, Ayşe Betül; Bostancı Ergen, Evrim; Özdemir, Pelin; Aktaş, Özgür; Giray, Burak; Kabaca Kocakuşak, Canan (Kare Publishing, 2023)
Objective: Bleeding is the most common complication of conization of cervix. Hemostatic sutures, intraoperative ferric subsulfate, or vasopressin can be used when intraoperative bleeding occurred, whereas oral tranexamic acid (TA) may be used for post-operative bleeding. In this study, we aimed to find out whether intraoperative cervical TA administration in patients undergoing conization caused changes in the amount of intraoperative bleeding and post-operative hemogram. Material and Methods: Patients who have undergone cervical conization between January 2019 and July 2019 in Zeynep Kamil Health Application and Research Center Gynecological Diseases and Birth Clinic were evaluated. One hundred and five patients were included to our study. One ampoule of 10% TA was applied cervically to 47 of these patients. Both groups were evaluated in terms of measuring the intraoperative amount of blood in the aspirator, changes in post-operative hb/htc/plt values compared to the pre-operative values, and the rate of post-operative bleeding. Results: In our study, the amount of intraoperative hemorrhage and pre-operative hemoglobin, hematocrit, and platelet values compared to the post-operative values were found to be similar in both groups. Conclusion: Although TA has been shown to be effective on hemorrhage in benign gynecologic operations, menorrhagia, and postpartum hemorrhages, no significant effect on hemorrhage in conization with cervical TA administration has been demonstrated.
Keywords: Cervical Cytology; Cervical Intraepithelial Neoplasia; Conization; Human Papilloma Virus; Tranexamic Acid